A Study of Damage Patterns on Passenger Cars Involved in Road Traffic Accidents. (2nd January 2019) - Kurebwa, Joseph; Mushiri, Tawanda
Abstract : Health emergencies occur in passenger cars where victims do not have immediate access to either layperson or professional, proper medical services, resulting in deterioration of their health or death. Installation of robotic first aid system for passenger-car occupants has been proposed. This study is part of a larger work of designing the system and seeks to identify the safest location inside the vehicle for it to survive any form of impact in a crash and retain the ability to assist the victims. The study population comprised 70 passenger cars (14 automakers across 7 segments) involved in road traffic accidents, which had been recovered by a roadside vehicle assistance company based in Harare, Zimbabwe, and were on the company's premises on September23 r d, 2017. Vehicle damage was rated considering direction of force in comparison to a clock-point diagram, area damaged, and the damage severity on a scale of 1 to 7, following an official vehicle damage guide for traffic crash investigators. Data were analysed in Microsoft Office Excel 2016. In cases where vehicles were damaged in more than one area, all areas were recorded, hence 95 points of impact were analysed. Damage direct to the front denoted by 12 on the clock-point was the most common at 26%. This was compatible with the rate of frontal damage on vehicles, which was the highest at 51%, followed by the right and left sides that had 22% and 19%, respectively, the rear at 6%, and lastly the top (due to 2 recorded rollovers) at 2%. 56% of the damaged areas had a severity rating of either 5, 6, or 7. By eliminating all areas which had received damage in the study population, the robotic first aid system's best chances of car crash survival are at the middle, towards the floor of the vehicle. It is advisable that the system does not depend on components in the proximity of the vehicle's body as they are prone to damage in crashes. There is need for further research into the magnitude of impact that could reach the middle of different vehicles to define the strength of the robotic first aid system.